ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT SURABAYA TERHADAP PENGGUNAAN DOMPET DIGITAL GOPAY - Febrina Rahardi; Novi Marlena (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
This study aims to determine, explain, and analyze whether cultural, social, personal, psychological, price, place, promotion, and product factors affect the interest of the people of Surabaya city and also want to know whether the dominant factor influences the interest of Surabaya people in using the Gopay digital wallet. In this study, the population used was all Gopay digital wallet users in the city of Surabaya using the